2013
DOI: 10.1111/jgh.12310
|View full text |Cite
|
Sign up to set email alerts
|

Worse outcome of sorafenib therapy associated with ascites and Child‐Pugh score in advanced hepatocellular carcinoma

Abstract: CP score was more important than CP class in predicting the outcome of sorafenib therapy in patients with advanced HCC. Among the CP score components, presence of ascites was a significant prognostic factor, especially in CPB7 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…It plays an important role in prognostic score for a variety of tumors, such as Gleason score for prostate cancer [6], Child-pugh classification for hepatocellular carcinoma [7], SBR, WHO score for breast cancer [8], but the prognostic effect of histopathology has never been reported in gastric cancer. Moreover, there is not any effective way to identify the prognosis of early gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important role in prognostic score for a variety of tumors, such as Gleason score for prostate cancer [6], Child-pugh classification for hepatocellular carcinoma [7], SBR, WHO score for breast cancer [8], but the prognostic effect of histopathology has never been reported in gastric cancer. Moreover, there is not any effective way to identify the prognosis of early gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, it was recently demonstrated that ideal therapeutic results were not achieved by sorafenib in patients with advanced HCC with CP class B (9). In such patients, we identified a subgroup exhibiting a better clinical outcome when treated with the split-dose FMP chemotherapeutic regimen, simply by assessing the AFP level and/or the GALNT14 genotype.…”
Section: Discussionmentioning
confidence: 89%
“…[39, 40] A real world cohort reported significantly decreased overall survival with sorafenib in Child-Pugh B compared to Child-Pugh A cirrhotics. [41] Likewise, post-marketing studies in entecavir for chronic HBV infection show lower proportions of ALT normalization than was shown in registration trials. [42]…”
Section: Discussionmentioning
confidence: 99%